The best efficacy in herbicides application towards oil palm seedling management / Muhammad Fakhruddin Kamarul - Kamarul, Muhammad Fakhruddin (Faculty of Plantation and Agrotechnology, 2019)
The spray application of agrochemical is effective but inefficient. Generally, the performance of the pesticides will be effective in consistence with the decrease of droplets sizes. The field study was carried out to compare pesticide equipment which are the conventional knapsack sprayer (CKS) and motorised mistblower. It was also carried out to discover the interaction of seedlings with systemic pesticide and non-systemic pesticide. This theory, as tested at the field experiment, was done with oil palm seedlings at the age of 5 months before the first culling process occurs. The pesticides application was performed once per month to eradicate pests and diseases in the oil palm nursery. The conventional knapsack sprayer was recorded to produce medium sized droplets (≥150 μm). Meanwhile, motorised mistblower was seen to produce fine sized droplets (≤150μm). A significant difference was identified when using the conventional knapsack sprayer and the motorised mistblower. However, there were no variances discovered between the use of systemic and non-systemic pesticide. The effectiveness of spraying application factors in the droplets size in order to find the correct choices and the best use of different pesticide equipment. The result of this study measures the number of oil palm seedlings that have been culled as indicators to make the comparison between conventional knapsack sprayer and motorised mistblower. The estimation of total loss and total cost per hectare were calculated to find the highest loss of oil palm seedling. Each seedling was recorded at a price of RM12.00.